Small Group Learning for Understanding the Specialized Language in students of occupational Health - Seyedeh Negar Assadi (Tabriz University of Medical Sciences, 2017)
Background: Learning methods are important in education, especially in some difficult lessons such as specialized or technical language. Instructors can use suitable and practical methods in these situations. The objective of this study was to compare the results of various educational methods for learning specialized language in occupational health students. Methods: This study was a semi-experimental study conducted in the Health School of Mashhad among occupational health students using the approved curriculum; a course of specialized language was taught with attention to educational methods. Three educational methods were used: small group learning in group A (n = 24), lecture in group B (n = 26) and reading with use of audio-visual devices in group C (n = 25). Change in learning was determined and results were compared among the three groups of participants, with results of exams analyzed using SPSS 16. analysis of variance (ANOVA) was used since the data was normalized, and significance was calculated at P < 0.05. Results: The mean grade in specialized language in group A was 16.66 (2.19), 10.93 (2.41) in group B and 14.74 (3.25) in group C. All of the methods had significant differences among each other, with P < 0.05. Participatory discussion had the highest mean (group A). The relative risk for group A was 1.56 (1.12-2.51). Conclusion: According to the total results, small group learning is the best educational method for learning specialized language for occupational health students.